Microbial-Assisted Wheat Iron Biofortification Using Endophytic Bacillus altitudinis WR10 - Sun, Zhongke; Yue, Zonghao; Liu, Hongzhan; Ma, Keshi; Li, Chengwei (Frontiers in Nutrition, 2021)
Microbial-assisted biofortification attracted much attention recently due to its sustainable and eco-friendly nature for improving nutrient content in wheat. An endophytic strain Bacillus altitudinis WR10 (B. altitudinis WR10) that showed sophistical regulation of iron (Fe) homeostasis in wheat seedlings, inspired us to test its potential for enhancing Fe biofortification in wheat grain. In this study, assays in vitro indicated that WR10 has versatile plant growth promoting (PGP) traits and bioinformatic analysis predicted its non-pathogenicity. Two inoculation methods, namely seed soaking and soil spraying with 107cfu/mL WR10 cells were applied once before sowing of wheat (Triticum aestivum L. cv. Zhoumai 36) in field. After wheat maturation, evaluation of yield and nutrients showed significant increase of the mean number of kernels per spike (KPS), and the content of total nitrogen (N), potassium (K), and Fe in grains. At the grain filling stage, the abundance of Bacillus spp. and content of N, K, and Fe in the root, the stem and leaf were also increased in nearly all tissues, except Fe in the stem and leaf. Further correlation analysis revealed a positive relationship between the total abundance of Bacillus spp. and the content of N, K, and Fe in grains. Seed staining confirmed the enhanced accumulation of Fe, especially in the embryo and endosperm. Finally, using a hydroponic co-culture model, qPCR quantification indicated effective colonization, internalization, translocation and replication of strain WR10 in wheat within 48 hours. Collectively, strain WR10 assisted successful Fe biofortification in wheat in field, laying a foundation for further large-scale investigation of its applicability and effectiveness.